Regular Physical Activity and Vascular Aging - M.M. Antunes, Bárbara; E. Rossi, Fabrício; M. Cholewa, Jason; S. Lira, Fábio (Current Pharmaceutical Design, 2016)
Background: Aging and low physical activity are associated with the development of diseases (hypertension, type 2 diabetes, dyslipidemia, obesity) marked by chronic low-grade inflammation. Cardiovascular disease is the most common cause of death worldwide, while exercising muscle tissue can increase the secretion of myokines that can reestablish a possible inflammatory process in virtue of the anti-inflammatory effect. Methods: The objective of this review is to focus on molecular mechanisms involved between different kinds of exercise and cellular oxidative stress, and the emerging therapeutic strategies which have the potential to promote benefits in vascular health. Results: Regular exercise increases shear stress, mitochondrial biogenesis, and upregulates mitochondrial antioxidant system, inducing anti-inflammatory actions, such as suppression of TNF-α which may offer protection against TNF-α-induced vascular impairment. Conclusion: Exercise training of various durations and intensities appears to prevent and restore the age-related impairment of endothelial function, likely through the restoration of NO availability, reduction in oxidative stress, and turnover of the apoptotic process in the endothelium, thus minimizing vascular inflammation and decreasing the formation of atherosclerotic plaques.
Keywords: endothelial dysfunction